انتفاء المسؤولية الجنائية للقاذف في النقد الصحفي الهادف - د. مجيد خضر احمد السبعاوي (PROSPECTIVE RESEARCHES, 2023)
Practicing of the right if journalitive indestructive criticism under the freedom of opinion, declaration and journalism, it starts from the important role, it is social, cultural and calendaral role, under the democratical conceptions , and under the legitimate, constitutional and lawful , for doing its moral duty , for understanding of society and uncovering all defects by flexibility and transparency aim to calendar for developing of society. So that , we should reduce the administrative and lawful barriers. But there are several conditions to be criticism permissioned, and the criminal protectection possibled :first , the event should be stable, second, it should be important for society, third, the critcism should be suitable, fourth, the critic should be good faith, fifth, the criticism should belong with writing not to writer, sixth, it should aim to the public benefit, and other conditions by which the criminal act becomes justified.